How to get shortlisted for medical jobs. Issue 6 (July 2017) - Gundogan, Buket; Koshy, Kiron; Whitehurst, Katharine; Fowler, Alex; Agha, Riaz
Abstract : Progressing up the medical career ladder is a tough business. Most medical and surgical applications center the requirement for a holistic, balanced individual. As a result, there are usually specific marking criteria in predefined sections. This article provides a guide into what employers are looking for and how best to build your portfolio in these areas.